Optimalisasi Manajemen Lembaga Pendidikan Nonformal melalui Penataan Jadwal, Pelatihan Guru, dan Pendampingan Santri - Zad, Muhammad Choiru; Dahlia, Dahlia; Maufur, Miqdam (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2025)
The community service program at TPQ Al Huda in Kerug Munggang Hamlet, Majaksingi Village, Borobudur Subdistrict, aims to improve the quality of Islamic education management through the Asset Based Community Development (ABCD) approach with the stages of discovery, dream, design, define, and destiny. The results of the activities show that the main assets of TPQ are teachers, students, and community support. Based on these assets, work programs were formulated, such as schedule arrangement, teacher task distribution, creative method training, and student mentoring. The implementation was carried out participatively with KKN students, teachers, and the community. The evaluation showed an increase in schedule regularity, creativity in learning methods, student motivation, and community support for the sustainability of the institution. Overall, the application of asset-based Islamic education management was able to strengthen the quality of Al-Qur'an learning and foster sustainable collaboration between TPQ, the community, and students in the management of non-formal educational institutions.